THREE STATE LOGIC PROBE - Adi Faizal; Drs. Lingga Hermanto, MMSI (Jurnal Sistem Komputer, 2005)
Created a logic level detection circuit of a digital circuit. This circuit has the ability to 3 (three) logic level digital signal is typically defined as follows: Level of high voltage (High), Level low voltage (Low) and the threshold voltage level (Thereshold). The ability of  this series allows a digital circuit analysis to help level the better. In this series of tests in particular applied to the gates of the base.